AI-29 Metabolome checkpoints of MTOR activation and clinical responsiveness in SLE. (31st August 2016) - Perl, Andras; Lai, Zhiwei; Oaks, Zachary; Asara, John; Hanczko, Robert; Kelly, Ryan; Phillips, Paul
Abstract : Background: The mechanistic target of rapamycin (mTOR) serves as a metabolic sensor of genetic and environmental cues that effectively regulates physiological T-cell activation and lineage specification. mTOR complex 1 (mTORC1) promotes pro-inflammatory T-cell development, B-cell activation and production of antinuclear autoantibodies (ANA) both in patients and mice with systemic lupus erythematosus (SLE). Therefore, we initiated a prospective clinical trials with rapamycin and N-acetylcysteine (NAC), the latter of which blocks redox-dependent mTORC1 activation. Materials and methods: 36 SLE patients were enrolled in a 3-month placebo-controlled trial with NAC which involved 212 metabolic and immunological markers prior to enrollment, and follow-up at 1-month intervals. 42 healthy controls, matched at each visit for age, ethnicity, and gender, were studied in parallel. 258 metabolites were measured mass spectroscopy. 40 SLE patients were enrolled in a 12-month open-label intervention with rapamycin; patients and 88 matched controls were studied in parallel at 3-month intervals. Analysis of pathways, area under the curve (AUC) logistic regression, two-factor (NAC versus placebo) time series within individual subjects were performed with Metaboanalyst. SLEDAI, BILAG, and SRI disease activity indices were calculated. Results: Rapamycin reduced disease activity in 126 ± 18 days as evidenced by well-tolerated rapamycin plasma levels of 8.7 ± 1.2 ng/ml, which was within the targeted therapeutic range of 6–15 ng/ml. SLEDAI disease activity scores were reduced to 5.7 ± 1.0 from 11.8 ± 1.1 at baseline (p = 0.0028). Among the patients who completed the 1 year intervention, a SLE Responder Index of 64.3% was achieved. Rapamycin inhibited the pro-inflammatory T cell skewing (Figure 1 ), including the expansion and IL-4 production of CD4 - CD8 - double-negative (DN) T cells and reversed the contraction of CD4 + CD25 + FoxP3 + regulatory T cells (Tregs) and CD4 + and CD8 + central and effector memory T cells. Treatment with NAC exerted lesser but statistically signi?ficant reduction of SLEDAI and BILAG over 3-month. Metabolome changes involved 27 of 80 KEGG pathways at FDR p < 0.05 with most prominent impact on the pentose phosphate pathway (PPP). While cysteine was depleted, a PPP-regulated compound, kynurenine, was the most increased metabolite and the top predictor of SLE (AUC = 0.859). Kynurenine directly stimulated mTORC1 activity of DN T cells in vitro . Relative to placebo, NAC reversed these metabolite changes in vivo. Conclusions: The PPP-connected accumulation of kynurenine and its stimulation of mTORC1 are identified as metabolic checkpoints in lupus pathogenesis. Blockade of mTORC1 has the premise of safe and effective treatment in SLE. Acknowledgements: This work was supported in part by grants RO1 AI072648 and R01AT004332 from the National Institutes of Health and Investigator-Initiated Research Grant P0468X1-4470/WS1234172 from Pfizer. Trial Registration Prospective Study of Rapamycin for the Treatment of SLE; ClinicalTrials.gov Identifier: NCT00779194 . Treatment trial of SLE with N-acetylcysteine; ClinicalTrials.gov identifier: NCT00775476 .